Synthesis, Structural Determination, and Antifungal Activity of Novel Fluorinated Quinoline Analogs - Xinpeng Sun; Wei Yu; Lijing Min; Liang Han; Xuewen Hua; Jianjun Shi; Nabo Sun; Xinghai Liu (Molecules, 2023)
A series of new fluorinated quinoline analogs were synthesized using Tebufloquin as the lead compound, 2-fluoroaniline, ethyl 2-methylacetoacetate, and substituted benzoic acid as raw materials. Their structures were confirmed by 1H NMR, 13C NMR, and HRMS. The compound 8-fluoro-2,3-dimethylquinolin-4-yl 4-(tert-butyl)benzoate (2b) was further determined by X-ray single-crystal diffraction. The antifungal activity was tested at 50 μg/mL, and the bioassay results showed that these quinoline derivatives had good antifungal activity. Among them, compounds 2b, 2e, 2f, 2k, and 2n exhibited good activity (>80%) against S. sclerotiorum, and compound 2g displayed good activity (80.8%) against R. solani.